2010
DOI: 10.3748/wjg.v16.i22.2793
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the closure time of postoperative enterocutaneous fistulas with fibrin sealant

Abstract: Closure time was significantly reduced with the use of fibrin sealant, and oral feeding was resumed faster. We suggest the use of fibrin sealant for the management of stable enterocutaneous fistulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Avalos-González et al [40] reported that a fibrin sealant could reduce the closure time of stable enterocutaneous fistulas. The AFP, which is made of lyophilized porcine intestinal submucosa, has the same effect on an anal fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Avalos-González et al [40] reported that a fibrin sealant could reduce the closure time of stable enterocutaneous fistulas. The AFP, which is made of lyophilized porcine intestinal submucosa, has the same effect on an anal fistula.…”
Section: Discussionmentioning
confidence: 99%
“…One of them is adjuvant treatment to achieve hemostasis in diffuse bleeding and to achieve tissue sealing and/or adhesion in surgical treatment. In this regard, fibrin-based biological adhesive is being used in clinical practice by many gastrointestinal surgeons to prevent fistula formation in gastrointestinal anastomoses, achieving a high percentage of success in a short period of time [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…One of the identified studies was for pancreaticoduodenectomy, 28 and one was for esophagojejunal anastomosis, 18 while the other 16 studies were for different procedures in the upper colorectum, including anal fistula repairs and laparoscopic gastric bypass surgeries. 1,2,7,10,[13][14][15][16]19,26,27,32,36,37,40,41,44 Many of these studies suggest a relationship between FS and a reduction in leakages and other complications such as bleeding. However, these studies were not powered to find statistical significance in results.…”
Section: Discussionmentioning
confidence: 99%